Electrochromism and Swelling of Polypyrrole Membranes: An Electrochemical and Ellipsometric Study - Zerbino, Jorge Omar (2011)
The growth of polypyrrole (Ppy) layers on gold electrodes in nearly neutral pH solutions is analysed using “in situ” voltametric and ellipsometric techniques. Different film structures are obtained depending on the potentiodynamic programme and the composition of the electrolyte. More compact dodecylsulphate-(DS) doped Ppy layers were grown at 1.2 V versus RHE than those obtained by applying a higher potential. The more compact layers correspond to the growth of an oxidised Ppy/DS layer that shows low pseudo capacity behaviour. After dipping, the doped Ppy/DS film in KCl solution-significant variations in optical indices and thickness are detected as a function of the applied potential. Higher electrochromism as well as decrease in film thickness after cathodisation is achieved. The optical indices and the thickness of the Ppy layer formed under different applied potential/time programmes are estimated.